RELEVANSI FAKTOR KEGEMILANGAN SAINS ISLAM DENGAN DUNIA ISLAM MASA KINI (Relevance Factor of Islamic Sciences’ Excellence towards Muslim World Today) - Sidik @Mat Sidek, Roziah (Journal of Al-Tamaddun, 2012)
This article analyses the relevance of the factors of scientific excellence in the Islamic civilization to the present Islamic world. Accordingly, it exposes the factors which led to scientific excellence in the Islamic civilization before analysis of their relevance to the present Islamic world. This article is intended to assess the relevance of the said factors so as to enable a quantum leap in scientific excellence of the present Islamic world. The jusitification for it is that if a given factor played a role, then by the same token, it is not impossible that the same can be done to restore scientific excellence in the present Islamic world. The writer uses the approach of detailed analysis of contents of sources in various languages to deduce the intended factors. Results show at least seven factors which spurred scientific excellence in Islamic civilization. However, the writer chooses to analyse only five factors, which are, the spirit of Islam which encourages intellect, the meeting of Islamic civilization and ancient civilizations in the Middle East, the positive attitude of the rulers, the role of private individuals and the science policy. The writer also added one more factor, that is, collaboration between Muslims and non-Muslims. Although not many sources refer to this as a contributory factor to scientific excellence in Islamic civilization, the cooperation forged between the two parties did assist to spur scientific excellence onto the world scene. The said factors thus prove their relevance to the present Islamic world.